ASUHAN KEPERAWATAN PADA NY.F DENGAN DIABETES MELLITUS TIPE 2 DI RUANG PEJUANG RSUD BANGKINANG - mariaulfa ulfa; Yenny Safitri; Nila Kusumawati; Indrawati (El-Emir Institute, 2025)
Diabetes mellitus (DM) is a chronic disease characterized by a significant increase in blood glucose levels. This condition is caused by a deficiency of the hormone insulin or impaired insulin function in glucose metabolism. Signs and symptoms of diabetes mellitus include polyuria, polydipsia, polyphagia. The aim of this research is to examine and implement nursing care for patients with type II diabetes mellitus in the fighting room at Bangkinang Regional Hospital in 2025. This research method uses a descriptive research design in the form of a case study. Subjective in the case report is Mrs. During the assessment, the client feels weak, has no appetite, stomach ache, has nausea and vomiting, has a headache, and urinates frequently. Researchers formulated the main problem with the nursing diagnosis of blood glucose instability related to hyperglycemia (D.0027). The intervention given is monitoring blood glucose levels. In implementing nursing actions for Mrs.F with type II diabetes mellitus, they were carried out according to the nursing plan that had been prepared. The result of a three-day nursing visit to the client was that the problem was resolved. Nursing evaluation for three days on this client as a guide for researchers: as a goal for conducting research on Diabetes Mellitus, campus: as a reference in providing nursing care to patients.